Concise account of recent S(N)2 ` grignard coupling reactions in organic synthesis - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
Over the past few decades studies oil controlling the chemo-, regio- and stereoselectivities of allylic Substitution reactions have been well documented in the literature and the S(N)2' Grignard coupling reaction has emerged as a very powerful tool ill selective carbon-carbon bond formation. This review focuses on all the recent synthetic developments in this special class of reactions. 1 Introduction 2 S(N)2' Grignard Coupling Reactions with Allylic Substrates 2.1 Allyl Halides 2.2 Allyl Acetates 2.3 Allyl Carbonates 2.4 Allyl Carbamates 2.5 Allyl Ethers 2.6 Allyl Silyl Ethers 2.7 Allyl Epoxides 2.8 Allyl Aziridines 2.9 Allyl Oxazolidinones 2.10 Allyl Thioethers 2.11 Allyl Benzotriazoles 2.12 Oxabicyclic Alkenes 2.13 Azabicyclic Alkenes 2.14 Oxa-azabicyclic Alkenes 3 S(N)2' Grignard Coupling Reactions with Propargyl Substrates 3.1 Propargyl Acetates 3.2 Propargyl Silyl Ethers 3.3 Propargyl Epoxides 3.4 Propargyl Aziridines 3.5 Propargyl Dithioacetals 3.6 Propargyl Thioethers 4 S(N)2' Grignard Coupling Reactions with Bromoallenes 5 S(N)2' Grignard Coupling Reactions in Natural/Unnatural Product Synthesis 6 Conclusions.
Keywords: allylic substrates; bromoallenes; chiral/achiral S(N)2 ` Grignard coupling reactions; Natural products; propargyl Substrates

Application of hydrolytic kinetic resolution (HKR) in the synthesis of bioactive compounds - Kumar, Pradeep; Naidu, Vasudeva; Gupta, Priti (Tetrahedron, 2007)
Keywords: Biological activity; bis-epoxides; Hydrolytic kinetic resolution; meso-epoxides; Natural products; synthesis; terminal epoxides

Short and efficient synthesis of rubrolide E - Chavan, Subhash P.; Pathak, Ashok B.; Pandey, Ankur; Kalkote, Uttam R. (Synthetic Communications, 2007)
Short and efficient synthesis of rubrolide E from commercially available 4-methoxyacetophenone, employing ring-closing metathesis, Knoevenagel condensation, and Reformatsky reactions, are the key steps are described.
Keywords: antibiotics; antitumor; Epoxide; Natural products; Total synthesis

Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Total synthesis of pulchellalactam via an RCM strategy - Chavan, Subhash P.; Pathak, Ashok B.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthetic Communications, 2007)
Total synthesis of (Z) pulchellalactam, a CD protein tyrosine phosphatase inhibitor, from commercially available methallyl chloride employing ring-closure metathesis (RCM) as a key step is described.
Keywords: alkaloid; Natural products; pulchellalactam; RCM; Total synthesis

Tandem aza-michael-condensation-aldol cyclization reaction: approach to the construction of DE synthon of (+/-)-camptothecin - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synlett, 2008)
An efficient synthesis of the DE ring of camptothecin, employing a Reformatsky and a tandem one-pot, three-step transformation involving aza-Michael reaction, condensation with ethyl malonyl chloride followed by intramolecular `aldol' reaction to furnish the dihydropyridone derivative from commercially available starting materials, has been achieved.
Keywords: Aldol cyclizations; alkaloids; antitumor; Natural products; Reformatsky reaction

Hydrolytic kinetic resolution as an emerging tool in the synthesis of bioactive molecules - Kumar, Pradeep; Gupta, Priti (Synlett, 2009)
A variety of racemic epoxides mainly derived from terminal olefins, such as aliphatic epoxides, multifuncitonalized epoxides and amine-substituted epoxides, have been successfully resolved into the enantiomerically pure epoxides and diols using Jacobsen's hydrolytic kinetic resolution (HKR) method. The chiral epoxides thus prepared were further elaborated by synthetic manipulation to provide a variety Of Compounds of biological interest. A general synthetic strategy for the construction Of S synlanti-1,3-polyol systems using iterative HKR has been developed, which was subsequently utilized in the synthesis of natural products with a broad range of biological activity. The protocol for the 1,3-polyols was also further extended to the synthesis of 1,3-amino alcohols.
Keywords: Biological activity; Hydrolytic kinetic resolution; Natural products; synthesis; terminal epoxides

Total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from citraconic anhydride, the first total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol has been demonstrated via a stepwise route involving generation of an apiitol derivative followed by benzoylation.
Keywords: (+/-)-1; 3; 4; 5-tetragalloylapiitol; allylic hydroxylation; Natural products; osmium tetroxide

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Construction of the 5,10b-phenanthridine skeleton using [3+2]-cycloaddition of a non-stabilized azomethine ylide: total synthesis of (+/-)-maritidine and (+/-)-crinine alkaloids - Pandey, Ganesh; Gupta, Nishant R.; Gadre, Smita R. (European Journal of Organic Chemistry, 2011)
Vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton 1 are constructed simultaneously in one step by the [3+2]-cycloaddition of non-stabilized azomethine ylide 9, generated by sequential double desilylation of 10 utilizing silver(I) fluoride as a one-electron oxidant. The regioas well as stereochemical origin of this cycloaddition reaction is explained through a favorable transition state 9''. The strategy is successfully applied for the total synthesis of the biologically active alkaloids (+/-)-maritidine (1a), (+/-)-crinine (1b), and their analogues (1d, 1e, and 1f).
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Natural products; Ylides

Carbohydrate-based synthesis of the C13-C22 fragment of amphidinolide X - Gurjar, Mukund K.; Yellol, Gorakh S.; Mohapatra, Debendra K. (European Journal of Organic Chemistry, 2012)
A facile carbohydrate-based route was developed for the synthesis of the tetrahydrofuran (C13C22) fragment of amphidinolide X. Starting from L-sorbose, the key reactions followed include the stereoselective synthesis of a quaternary center at C1, BartonMcCombie deoxygenation at C2, Mitsunobu inversion at C3, and chain elongation by a Wittig reaction at C5.
Keywords: Cytotoxicity; Macrolides; Mitsunobu inversion; Natural products; Wittig reactions

InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis

Palladium-catalyzed routes to geranylated or farnesylated phenolic stilbenes: synthesis of pawhuskin C and schweinfurthin J - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2012)
Starting from double MOM-protected phloroglucinol, the facile total syntheses of bioactive natural products pawhuskin C and schweinfurthin J were accomplished in good overall yields. The Heck, Stille, or Suzuki coupling reactions of two different electron-rich phenolic segments bearing geranylated or farnesylated units were involved in the decisive step. The Sonogashira coupling reaction followed by palladium-catalyzed chemo-and stereoselective cis-reduction of an alkyne unit and subsequent isomerization to give the desired natural products is also described.
Keywords: geranylated or farnesylated stilbenes; Natural products; palladium-catalyzed coupling reactions; phloroglucinol; Total synthesis

Total synthesis of the putative structure of xylarinol B - More, Atul A.; Ramana, Chepuri V. (Chemistry-An Asian Journal, 2014)
The total synthesis of the putative structure of xylarinolB is described and the need to revise its structure is demonstrated. The central benzoxepine skeleton was constructed by employing a cobalt-mediated bimolecular [2+2+2] Reppe-Vollhardt alkyne cycloaddition reaction.
Keywords: Chiral pool; cobalt; Natural products; structure elucidation; Total synthesis

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis

First enantioselective synthesis of surinamensinol B and a non-natural polysphorin analogue by a two-stereocentered hydrolytic kinetic resolution - Lalwani, Komal G.; Sudalai, Arumugam (European Journal of Organic Chemistry, 2015)
An efficient and economical approach to the synthesis of antitumor and anti-inflammatory surinamensinol B (1) and antimalarial polysphorin analogue 2 has been achieved with high enantiomeric purity (96% ee) by starting from commercially available 3,4,5-trimethoxybenzaldehyde. The key steps of the strategy include a Co-catalyzed two-stereocentered hydrolytic kinetic resolution (HKR) of racemic 2[( methoxymethoxy)(3,4,5-trimethoxyphenyl)methyl] oxirane (13) as the chiral inducing step followed by a Mitsunobu reaction. Chiral epoxide 14 and chiral diol 15 were utilized in the syntheses of both compounds.
Keywords: Biological activity; Enantioselectivity; Kinetic resolution; Natural products; Total synthesis

Synthesis of yangjinhualine A - Deore, Prashant S.; Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2015)
Selective reduction of 3-(4-hydroxyphenyl)-2-methylmaleic anhydride provides access the corresponding gamma-hydroxybutenolide natural product yangjinhualine A.
Keywords: anhydrides; lactones; Natural products; reduction; Regioselectivity

Total and semi-syntheses of antimicrobial thuggacin derivatives - Franke, Jana; Bock, Martin; Dehn, Richard; Fohrer, Joerg; Mhaske, Santosh B.; Migliorini, Antonella; Kanakis, Argyrios A.; Jansen, Rolf; Herrmann, Jennifer; Mueller, Rolf; Kirschning, Andreas (Chemistry-A European Journal, 2015)
The total and semi-synthesis of 13 new macrolactones derived from thuggacin, which is a secondary metabolite from the myxobacterium Sorangium cellulosum, are reported. The thuggacins have attracted much attention due to their strong antibacterial activity, particularly towards Mycobacterium tuberculosis. This study focuses on 1) thuggacin derivatives that cannot equilibrate by transacylation between the three natural thuggacins A-C, 2) the roles of the thiazole ring, and 3) the hexyl side chain at C2. Semi-synthetic O-methylation at C17 suppressed the transacylations without a substantial loss of antibacterial activity. Exchanging the C17-C25 side chain for simplified hydrophobic chains led to complete loss of antibacterial activity. Exchange of the thiazole by an oxazole ring or removal of the hexyl side chain at C2 had no substantial effect on the biological properties.
Keywords: antibiotics; lactones; Natural products; synthesis design; Total synthesis

Chemoenzymatic access to (+)-artabotriol and its application in collective synthesis of (+)-grandiamide D, (-)-tulipalin B, (+)-spirathundiol, and (+)-artabotriolcaffeate - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2016)
Starting from dimethyl (+/-)-2-hydroxy-3-methylenesuccinnate chemoenzymatic collective formal/total synthesis of enantiomerically pure bioactive natural products has been described via the advanced level common precursor (+)-artabotriol. An efficient enzymatic resolution with high enantiomeric purity, selective diester to diol reduction, and requisite dehydrative coupling reactions without any racemization are the significant topographies.
Keywords: (+)-artabotriol; collective synthesis; coupling reactions; dimethyl (+/-)-2-hydroxy-3-methylenesuccinate; Enzymatic resolution; Natural products; reduction

Enantioselective modular total synthesis of macrolides Sch725674 and C-4-epi-Sch725674 - Sharma, Brijesh M.; Gontala, Arjun; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
The convergent total synthesis of Sch725674 has been accomplished by starting from (R)-1,2-epoxyheptane and assembling five modules in a highly stereoselective manner to give the final product in 6.6% overall yield. The same strategy was extended to the synthesis of its C-4 epimer. Key reactions of the synthetic pathway include a Jacobsen hydrolytic kinetic resolution of an epoxide followed by its regioselective opening through a Yamaguchi-Hirao alkynylation, and ring-closing metathesis reaction to furnish the unique 14-membered ring macrolactone. In addition, the influence of protecting groups on the efficiency of the ring-closing metathesis (RCM) macrocyclization has been studied to maximize its yields.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; Macrocycles; Metathesis; Natural products

Total synthesis of (-)-nardoaristolone B - Ople, Rohini S.; Handore, Kishor L.; Kamat, Nidhi S.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
A stereoselective total synthesis of (-)-Nardoaristolone B, a nor-aristolane sesquiterpenoid natural product with an unusual 3/5/6 tricyclic ring system is described. The highlights of the present work includes use of (+)-(R)-Pulegone as a chiral-pool starting material, ring-closing metathesis, allylic oxidation and stereoselective cyclopropanation. In addition, a new analogue of Nardoaristolone B (minor product from the final step) was isolated in pure form and fully characterized with the help of single-crystal X-ray analysis.
Keywords: Chiral pool; cyclopropanation; Nardoaristolone B; Natural products; Total synthesis

Achmatowicz reaction: A versatile tool in bioactive natural products synthesis - Mahajan, Pankaj S.; Humne, Vivek T.; Mhaske, Santosh B. (Current Organic Chemistry, 2017)
Achmatowicz reaction has emerged as an efficient tool in organic synthesis since its discovery in 1971 by Achmatowicz Jr. The original protocol went through several advantageous variations. Biocatalytic and metal catalyzed versions of this reaction are some of the significant achievements, which further enhanced its effectiveness. The pyranone product of the Achmatowicz reaction is a versatile building block for the synthesis of bioactive scaffolds, drugs and natural products. The present review covers the application of the Achmatowicz reaction in the synthesis of natural products and bioactive molecules reported from 1971 to date. It has been divided into seven sections on the basis of the core structures of the natural products synthesized utilizing the Achmatowicz reaction. We believe that this comprehensive review will attract many more organic chemists to explore its utility in organic synthesis, especially in the synthesis of bioactive natural products as well as drugs in their efficient and atom economical synthesis.
Keywords: Achmatowicz reaction; carbohydrates; Furanols; Natural products; pyranones; Total synthesis

First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin

First total synthesis of the proposed structure of pandangolide 1 - Show, Krishanu; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2018)
The first total synthesis of the proposed structure of pandangolide 1 is reported. The synthesis was carried out using both an organocatalytic approach and a chiral-pool approach. The required stereochemistry at C-3 and C-5 was installed by using an organocatalytic aldol reaction and a stereoselective ketone reduction. The construction of the 12-membered core was achieved by 2-methyl-6-nitrobenzoic anhydride-mediated Shiina lactonization. The structure of target molecule was confirmed unambiguously by single-crystal X-ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product.
Keywords: lactones; Macrocycles; Natural products; structure elucidation; synthesis design; Total synthesis

Transition-metal-catalyzed reactions involving arynes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Synthesis-Stuttgart, 2018)
The plethora of transformations attainable by the transition-metal-catalyzed reactions of arynes has found immense contemporary interest in the scientific community. This review highlights the scope and importance of transition-metal-catalyzed aryne reactions in the field of synthetic organic chemistry reported to date. It covers transformations achieved by the combination of arynes and various transition metals, which provide a facile access to a biaryl motif, fused polycyclic aromatic compounds, different novel carbocycles, various heterocycles, and complex natural products. 1 Introduction 2 Insertion of Arynes 3 Annulation of Arynes 4 Cycloaddition of Arynes 5 Multicomponent Reactions of Arynes 6 Miscellaneous Reactions of Arynes 7 Total Synthesis of Natural Products Using Arynes 8 Conclusion
Keywords: annulation; arynes; Cycloaddition; Insertion; multicomponent; Natural products; Transition Metal

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

Synthesis of 2-azabicyclo[m.n.0]-alkanes and their application towards the synthesis of strychnos and stemona classes of alkaloids - Majumder, Binoy; Pandey, Ganesh (European Journal of Organic Chemistry, 2020)
2-Azabicyclo[m.n.0]alkane ring systems, the conceptual precursors towards the synthesis of Strychnos and Stemona classes of alkaloids, were synthesized from tert-butyl 2-(phenylsulfonyl)-7-aza-bicyclo[2.2.1]hept-2-ene-7-carboxylate by alkyl Grignard reaction and intramolecular cyclisation of the in situ generated ring opening product 2. The synthesized cis-hexahydroindole 3 and cis-octahydro-benzo[b]azepine 5 scaffolds were utilized to construct the advanced intermediates 25 and 35, respectively, towards the synthesis of the corresponding Strychnos and Stemona classes of alkaloids.
Keywords: alkaloids; amines; Grignard reaction; Michael addition; Natural products

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction

Stereoselective strategies for the synthesis of functionalized cis-hydrindanes in natural product synthesis - Survase, Vijayanand U.; Handore, Kishor L. (European Journal of Organic Chemistry, 2025)
The cis-hydrindane motif is a bicyclic structure commonly found in many natural products that exhibit significant biological activity. This structural feature is present in a variety of bioactive compounds, particularly terpenoids, steroids, and alkaloids, which are known for their therapeutic potential, including anti-inflammatory, antimicrobial, antiviral, and anticancer properties. Due to its prevalence and biological relevance, the cis-hydrindane framework has attracted considerable attention from synthetic chemists, who have devoted substantial effort toward developing efficient and diverse methods for constructing this important motif. Many of the synthesized cis-hydrindane compounds have been used as key intermediates or building blocks in the total synthesis of complex natural products. This review provides an overview of strategic approaches for synthesizing functionalized cis-hydrindanes and its derivatives from 2000 to the present day, focusing on their application in natural product synthesis. By examining the diverse methods and their impact on natural product synthesis, this review will underscore the enduring importance of the cis-hydrindane framework in both synthetic organic chemistry and medicinal chemistry.
Keywords: annulation; Cis-hydrindane; Diel-Alder reaction; Natural products; Total synthesis